KURIKULUM ANAK JALANAN SEBAGAI BEKAL PENDIDIKAN ALTERNATIF - Mahfuzi Irwan; Adinda Yulfina (Journal Education for All : Media Informasi Ilmiah Bidang Pendidikan Luar Sekolah, 2022)
Alternative education is an alternative option for people who have limited access to education, and the implementation of alternative education has a significant contribution to achieving national education goals. Alternative education in Indonesia has various forms such as reading parks, children's centers, halfway houses, natural schools and homeschooling. Alternative education is closely related to non-formal education because non-formal education is an effort to provide education to people who are unable to get an education. One of the targets of alternative education is street children. The curriculum and learning for street children provided must be in accordance with the interests and needs of street children so that it can be an educational provision that will later lead to the independence of street children in their lives. The purpose of this study is to describe and analyze the training and course curriculum as an alternative education for street children and to find out the appropriate curriculum for street children through alternative education. The method used in data collection is a literature review and literature study from various sources.